2020
DOI: 10.3389/fvets.2020.00597
|View full text |Cite
|
Sign up to set email alerts
|

Selecting Dogs for Explosives Detection: Behavioral Characteristics

Abstract: Detection dogs are widely considered the most effective and adaptive method for explosives detection. Increases in emerging sophisticated threats are accelerating the demand for highly capable explosives detection, causing a strain on available supplies of quality canines worldwide. These strains are further compounded by rigorous behavioral standards required to meet mission-specific capabilities, leading to high rates of dogs disqualified from training or deployment. Ample research has explored the behaviora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 90 publications
(211 reference statements)
0
54
0
4
Order By: Relevance
“…While questionnaire assessments can be a cost-effective and efficient way of evaluating canine behavior, accurate scoring depends on familiarity with the dog in a variety of situations. Thus, questionnaires may not be feasible during procurements performed by unfamiliar individuals, and if reported by the dog’s owner/trainer, requires the reporting to be honest and accurate [ 3 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While questionnaire assessments can be a cost-effective and efficient way of evaluating canine behavior, accurate scoring depends on familiarity with the dog in a variety of situations. Thus, questionnaires may not be feasible during procurements performed by unfamiliar individuals, and if reported by the dog’s owner/trainer, requires the reporting to be honest and accurate [ 3 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…While independence is generally considered to be important to a detection dog’s ability to work autonomously without influence from or dependence on the handler [ 34 , 48 ], this measure was added to the evaluation to capture dogs’ cooperativeness. For example, dogs need to be responsive to handler commands, and a willingness to cooperate is considered to reflect trainability [ 3 ]. We recently reported that dogs that make eye contact with the handler during an unsolvable task, interpreted as a communicative signal, are more likely to be selected for a future detection role [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this observation supports previous research suggesting a complex interaction between temperament and problem-solving ability [ 29 ]. These and other behavioral factors should be considered when selecting dogs for olfactory learning research as well as selecting breeds for scent detection roles [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%